Media Cici Drama dalam Pembelajaran Teks Drama Kelas VIII (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Drama learning in grade VIII of Junior High School obtains several problems. These problems include students who are less active in participating in learning, intake of students in understanding drama material is low, and the learning media used are less varied. Therefore, teacher creativity is really needed, especially in presenting interesting and effective learning media. Based on that, this article is to study the media design for drama texts learning called "Cici Drama" (Laci Tujuh Kunci Drama). The method used in this research is descriptive qualitative method. The objectives of this study include describing the media, the criteria for selecting media, how to make media, how to use them in the classroom, and their strengths and weaknesses. The results showed that the appearance of "Cici Drama Media" had the right visuals and contents to achieve the goals of drama text learning in grade VIII. The way to make the media is relatively easy and does not require large costs. The way to use the media in the class tends to be easy and does not require special skills. For its weakness, this media requires any development by adding a slot on the right side of the main body for use in large classrooms.